Pengaruh Lingkungan Kampus, Media Pembelajaran, dan Fasilitas Kampus terhadap Motivasi Belajar Mahasiswa: Studi pada Mahasiswa Reguler Angkatan 2023 Fakultas Ekonomi dan Bisnis Universitas Budi Luhur Jakarta Selatan - Damar Bayu Prasetyo; Widi Wahyudi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the influence of three main factors—Campus Environment (X1), Learning Media (X2), and Campus Facilities (X3)—on Student Learning Motivation (Y) at the Faculty of Economics and Business, Budi Luhur University, South Jakarta. The research employed a quantitative design with a probability sampling approach using simple random sampling to ensure each student had an equal chance of being selected. Data were collected through structured questionnaires distributed to regular students of the Class of 2023, with a total sample size of 85 respondents. Descriptive analysis was conducted to summarize the primary data, while multiple linear regression analysis using SPSS version 22 served as the main analytical tool. The regression equation obtained was Y = 28.218 + 0.580X1 + 0.656X2 + 0.147X3 + €, indicating that each independent variable contributes differently to student learning motivation. The results demonstrate that the Campus Environment has a significant partial effect on Student Learning Motivation, highlighting the importance of a conducive academic and social atmosphere. Learning Media also shows a significant partial effect, suggesting that effective and innovative instructional tools can enhance student engagement and drive. Meanwhile, Campus Facilities have a positive but not significant partial effect, implying that while facilities support learning, other factors may play a stronger role. These findings underscore the need for universities to optimize both environmental and pedagogical aspects to boost student motivation and performance.